Refined control of CRISPR-Cas9 gene editing in Clostridium sporogenes: the creation of recombinant strains for therapeutic applications - Kubiak, Aleksandra M.; Claessen, Luuk; Zhang, Yanchao; Khazaie, Khashayarsha; Bailey, Tom S. (Frontiers in Immunology, 2023)
Realising the full potential of cancer immunotherapy is hindered by a lack of tumour-targeting strategies, resulting in irAEs and poor tumour penetration. Several targeted approaches seek to mitigate the drawbacks of high dose systemic delivery. One of these is the use of tumour-homing bacteria that are genetically engineered to produce a therapeutic. Clostridium sporogenes offers unique advantages for this approach: it forms spores and cannot germinate or grow in the presence of oxygen, typical of healthy tissue. This paper reports several developments that support this species as a vector for intratumoral delivery of therapeutics. The creation of a two-plasmid, tetracycline-inducible CRISPR-Cas9 system enables efficient addition or deletion of large sequences from the genome. Utilising this system, recombinant strains of two pro-inflammatory cytokines (IL-2 and GM-CSF) and a pro-drug converting enzyme were created, both as plasmid-and chromosome-based constructs. A comparative, temporal in vitro analysis of these strains revealed a substantial reduction of cytokine activity in chromosomebased constructs. To compensate for this loss, a 7.6 kb operon of proteolysis genes was deleted from the genome. Knockout strains showed an 8-to 10-fold increase in cytokine activity compared to parental strains.